Pelatihan Pembuatan Serbuk Sari Buah Tomat Guna Meningkatkan Nilai Tambah - Aditya, Dipa; Kusumawati, Nur Farida; Alam, Megawati Citra; Soesanto, Soesanto; De Vega, Steffan Albert Yoni (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Tomatoes as an agricultural commodity have perishable characteristics. This situation encourages efforts to increase longer shelf life, one of which is processed into fruit pollen products, where the product has eliminated water content in the manufacturing process. The purpose of this community service is to provide training in making tomato fruit pollen to increase added value. This Community Service activity was carried out in Pacet Village, Pacet District, Mojokerto Regency for 2 (two) months which included preparation, implementation and preparation of Community Service reports, which were carried out from September to November 2024. Data analysis was carried out descriptively qualitative. The stages of community service activities begin with coordination with the village hall to carry out training assistance in making tomato fruit pollen, then coordination with the head of the North Pacet Village RW to invite tomato farmers to attend the training event at the RW chairman's house. The process of making tomato fruit pollen includes: (1) Preparation of tools and materials; (2) Washing; (3) Tomato Fruit Slicing; (4) Drying; (5) Grinding; and (6) Packaging. Based on discussions with farmers, many farmers do not understand that tomato fruit can be processed into several agricultural products with higher added value such as when tomato fruit can be processed into flour or tomato pollen.